(3HQfGeL GdbGSe Hf jhSa Hf eMeO Hf Ydi Hf GdbGSe GdJLjHi GdHdfSi GdSHJis - (3GdbGSe Hf jhSa Hf eMeO Hf Ydj Hf GdbGSe GdJLjHj GdHdfSj GdSHJjs
(3ChdgG (B:s
(3CNHQfG GdTjN GdUGdM GdebQi GdaGVd CHh LYaQ Hf YHO GdQMef Hf YHO Gddg Hf GdTjN eSJhWf OeTb MQSgG Gddg JYGdi GdeYQha HGHf GdebjO s
(3BNQgG (B:s
(3hbO bQCJ hSeYJ ZjQ eG PcQ Ydi ZjQ ef PcQ hGbJUQJ Ydi gPG GdbOQ eNGaI GdEWGdI hGdEcKGQ MSHeG CYGf Ydjg GdhbJ Ef MSHfG Gddg hfYe Gdhcjd s
(3fSNI fajSIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1756) s
Keywords: (3GdMOjK h GdeUWdMs